Dissociative ionization and Coulomb explosion of ethyl bromide under a near-infrared intense femtosecond laser field. Issue 46 (23rd May 2015) - Teng, Chong; Wu, Hua; Zhang, Jian; Yang, Yan; Jia, Tianqing; Zhang, Shian; Sun, Zhenrong
<x xml:space="preserve">Abstract</x> The dissociation pathways for H2 and H2+ elimination from the parent ions C2H5Br+ and C2H5Br2+ are theoretically and experimentally demonstrated.